2020
DOI: 10.14336/ad.2019.0901
|View full text |Cite
|
Sign up to set email alerts
|

Targeting AMP-Activated Protein Kinase in Aging-Related Cardiovascular Diseases

Abstract: Aging is a pivotal risk factor for developing cardiovascular diseases (CVD) due to the lifelong exposure to various risk factors that may affect the heart and vasculature during aging. AMP-activated protein kinase (AMPK), a serine/threonine protein kinase, is a pivotal endogenous energy regulator that protects against various pathological alterations. In this report, we first introduced the protective mechanisms of AMPK signaling in myocardium, such as oxidative stress, apoptosis, inflammation, autophagy and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 92 publications
1
24
0
Order By: Relevance
“…For many years, it has been well-known that regular physical exercise can attenuate the major hallmarks of aging and promote health span by slowing down age-related degenerative processes [ 60 , 61 , 62 ]. Indeed, as we age, the loss of muscle mass and the risks of heart disease and dementia increases, and immune function becomes increasingly impaired [ 63 ]. For example, human aging is associated with skeletal muscle atrophy and functional impairment (sarcopenia), which can be partially reversed following six months of resistance exercise training [ 64 ].…”
Section: Ampk Signalingmentioning
confidence: 99%
“…For many years, it has been well-known that regular physical exercise can attenuate the major hallmarks of aging and promote health span by slowing down age-related degenerative processes [ 60 , 61 , 62 ]. Indeed, as we age, the loss of muscle mass and the risks of heart disease and dementia increases, and immune function becomes increasingly impaired [ 63 ]. For example, human aging is associated with skeletal muscle atrophy and functional impairment (sarcopenia), which can be partially reversed following six months of resistance exercise training [ 64 ].…”
Section: Ampk Signalingmentioning
confidence: 99%
“…These further result in endothelial dysfunction due to (1) nitric oxide inhibition in the endothelial cells of the blood vessels and (2) increased inflammation and fibrosis[ 109 ], eventually leading to increased risk of atherosclerotic CVD (marked as subsection A in Figure 1 ). Interestingly, many studies found that AMPK has a protective role in cardiac injury by acting against oxidative stress and turns into a potential therapeutic target in patients with diabetes and COVID-19[ 110 , 114 ]. Besides this link between oxidative stress, DM, and CVD, some recent studies have also pointed out a possible role of oxidative stress in the pathogenesis of COVID-19 related infections[ 112 , 113 , 115 , 116 ]; however, this is beyond the scope of this review.…”
Section: How Can the Interplay Between Dm And Covid-19 Increase The Rmentioning
confidence: 99%
“… 29 Recent evidences have shown that AMPK protects against oxidative stress in the heart under various pathological conditions. 30 Specifically, AMPK has been reported to exert antioxidant effects in the cardiovascular system by inhibiting the expression and activity of NOX. 31 , 32 Here, we found that SMS markedly increased AMPKα phosphorylation at Thr172 in the myocardium exposed to long-term high glucose.…”
Section: Discussionmentioning
confidence: 99%